Microbiology of aggressive periodontitis. (June 2014) - Könönen, Eija; Müller, Hans‐Peter
Abstract: For decades, Aggregatibacter actinomycetemcomitans has been considered the most likely etiologic agent in aggressive periodontitis. Implementation of DNA‐based microbiologic methodologies has considerably improved our understanding of the composition of subgingival biofilms, and advanced open‐ended molecular techniques even allow for genome mapping of the whole bacterial spectrum in a sample and characterization of both the cultivable and not‐yet‐cultivable microbiota associated with periodontal health and disease. Currently, A. actinomycetemcomitans is regarded as a minor component of the resident oral microbiota and as an opportunistic pathogen in some individuals. Its specific JP2 clone, however, shows properties of a true exogenous pathogen and has an important role in the development of aggressive periodontitis in certain populations. Still, limited data exist on the impact of other microbes specifically in aggressive periodontitis. Despite a wide heterogeneity of bacteria, especially in subgingival samples collected from patients, bacteria of the red complex in particular, and those of the orange complex, are considered as potential pathogens in generalized aggressive periodontitis. These types of bacterial findings closely resemble those found for chronic periodontitis, representing a mixed polymicrobial infection without a clear association with any specific microorganism. In aggressive periodontitis, the role of novel and not‐yet‐cultivable bacteria has not yet been elucidated. There are geographic and ethnic differences in the carriage of periodontitis‐associated microorganisms, and they need to be taken into account when comparing study reports on periodontal microbiology in different study populations. In the present review, we provide an overview on the colonization of potential periodontal pathogens in childhood and adolescence, and on specific microorganisms that have been suspected for their role in the initiation and progression of aggressive forms of periodontal disease.